Fetal cerebral-umbilical Doppler ratio in prediction of fetal distress in patients with preeclampsia - Jurišić Aleksandar; Jurišić Žaklina; Pažin Vladimir; Vasiljević Mladenko; Janković-Ražnatović Svetlana; Dragojević-Dikić Svetlana (Vojnosanitetski Pregled)
Bacground/Aim. The use of color Doppler ultrasonography provides noninvasive observation, confirmation and quantification of pathophysiological processes in fetoplacental circulation in pregnant patients. By blood vessel mapping and the obtained waves spectral analysis it is possible to evaluate vascular resistency of the fetus blood vessels. The aim of the study was to evaluate cerebral-umbilical pulsatility index ratio in fetal circulation in prediction of fetal distress in patients with preeclampsia. Methods. By measurement of pulsatility indices in medial cerebral and umbilical arteries in 400 patients with uncomplicated pregnancy, normal values were calculated for fetuses from 15-40 weeks. In our study group 70 patients with preeclampsia were included. Cerebralumbilical (C/U) ratio was calculated after pulsatility indices in medial cerebral artery and umbilical artery determining by the spectral Doppler analysis of flow velocity waveforms in these vessels. Fetal outcome was analyzed by measurement of the Apgar score at the 5th minute and fetal pH at birth. Results. The mean C/U ratio values in the third trimester of normal pregnancy were between 1.8 and 1.9. The mean C/U ratio values in the patients complicated with preeclampsia were significantly lower comparing to normal pregnancies (ANOVA, p < 0.05). The mean 5th minute Apgar score in the study group was 6.35 ± 1.58, and the mean fetal pH at birth was 7.16 ± 0.15. Linear regression test showed a highly significant correlation between low C/U ratio and fetal pH at birth in patients with preeclampsia (r = 0.49, p < 0.01). Conclusion. The C/U ratio values obtained from spectral Doppler analysis in fetal vessels showed a highly significant correlation with fetal pH at birth in the patients with preeclampsia. The results of our study confirmed the reliability of C/U ratio in estimation of fetal condition in preeclamptic patients. Very low C/U ratio values in patients with preeclampsia indicate that in these fetuses fetal acidosis and fetal distress may be expected.